Billy Elliot - Daldry, Stephen; Hall, Lee,|d1966-.; Universal Focus (Firm).; Studio Canal+.; Working Title Films; BBC Films; Arts Council of England; Tiger Aspect Pictures (Firm).; WT2 (Firm).; Universal City Studios; Magna Vision (Universal City, Calif. Universal Studios ; distributed in the Philippines by MagnaVision, 2001)
Eleven-year-old miner's son Billy Elliot is on his way to boxing lessons when he stumbles upon a ballet class. Billy secretly joins the class, knowing that his blue-collar family would never understand.
Originally released as motion picture in 2000.
Director of photography, Brian Tufano ; production designer, Maria Djurkovic ; editor, John Wilson ; costume designer, Stewart Meacham ; composer, Stephen Warbeck ; choreographer, Peter Darling ; directed by Stephen Daldry ; produced by Greg Brenman and Jon Finn ; written by Lee Hall.
Julie Walters, Gary Lewis, Jamie Draven, Jamie Bell, Adam Cooper.
MPAA rating: R.
VCD
Keywords: Teenage boys -- England -- Drama; Male dancers -- England -- Drama; Ballet dancers -- England -- Drama; Coal miners -- England -- Drama; Social classes -- England -- Drama; Dance